Efektivitas Model Pembelajaran Inkuiri Terhadap Hasil Belajar: The Effectiveness of the Inquiry Learning Model on Learning Outcomes - Khoiri, Nur (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
The purpose of the research is to know the effectiveness of inquiry learning model on student learning outcomes. Determination of the sample using cluster random sampling technique to obtain the experimental class and control class. Test for normality using Lilliefors test and test for homogeneity using Bartllet test. Hypothesis testing using t test and effectiveness of inquiry learning model showed by Gain test. Based on the analysis data, the result of this research is gotten with score tcount > ttable (4.93> 1.67), so Ho is rejected. This shows that the inquiry learning model is effective on learning outcomes. Gain analysis of an experimental class has high criterion (0.70) and the control class has medium criteria (0.48).